Mediating Effect of Self-Efficacy on the Relationship Between Medication Literacy and Medication Adherence Among Patients With Hypertension - Shen, Zhiying; Shi, Shuangjiao; Ding, Siqing; Zhong, Zhuqing (Frontiers in Pharmacology, 2020)
Background: Studies have reported that medication literacy had a positive effect on medication adherence in patients with hypertension. However, little is known about the mechanism underlying this relationship in patients with hypertension. Objective: The purpose of this study was to investigate the mediating effect of self-efficacy between medication literacy and medication adherence. Methods: A total of 790 patients with hypertension were investigated using the Chinese Medication Literacy Scale for Hypertensive Patients (C-MLSHP), the Morisky Medication Adherence Scale-8 (MMAS-8) and the Medication Adherence Self-efficacy Scale-Revision (MASES-R). Hierarchical regression and the bootstrap approach were used to analyze the mediating effect of self-efficacy on the relationship between medication literacy and medication adherence. Results: A total of 60.9% of hypertensive patients were low adherent to their antihypertensive drug regimens. Self‐efficacy had a significant positive correlation with medication literacy (r= 0.408, p < 0.001) and medication adherence (r = 0.591, p < 0.001). Self-efficacy accounts for 28.7% of the total mediating effect on the relationship between medication literacy and adherence to antihypertensive regimens for hypertensive patients. Conclusion: More than half of the hypertensive patients in the study were low adherent to antihypertensive regimens. Self-efficacy had a partial significant mediating effect on the relationship between medication literacy and medication adherence. Therefore, it was suggested that hypertensive patients’ medication adherence might be improved and driven by increasing self-efficacy. Targeted interventions to improve patients’ self-efficacy should be developed and implemented. In addition, health care providers should also be aware of the importance of medication literacy assessment and promotion in patients with hypertension.